2018
DOI: 10.1038/s41598-018-27377-2
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled hypertension increases risk of all-cause and cardiovascular disease mortality in US adults: the NHANES III Linked Mortality Study

Abstract: Clinical trials had provided evidence for the benefit effect of antihypertensive treatments in preventing future cardiovascular disease (CVD) events; however, the association between hypertension, whether treated/untreated or controlled/uncontrolled and risk of mortality in US population has been poorly understood. A total of 13,947 US adults aged ≥18 years enrolled in the Third National Health and Nutrition Examination Survey (1988–1994) were used to conduct this study. Mortality outcome events included all-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
189
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(209 citation statements)
references
References 27 publications
4
189
1
15
Order By: Relevance
“…e global burden of disease study reported that systolic blood pressure is associated with the highest burden among all risk factors, accounting for 10.2 million deaths and 208 million disability adjusted life years (DALYs) [1]. Hypertension is an important risk factor for chronic disease burden in India and a preventable contributor to death, disease, and disability [2,3]. Nearly 10.8% of all deaths in India are attributed to hypertension [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e global burden of disease study reported that systolic blood pressure is associated with the highest burden among all risk factors, accounting for 10.2 million deaths and 208 million disability adjusted life years (DALYs) [1]. Hypertension is an important risk factor for chronic disease burden in India and a preventable contributor to death, disease, and disability [2,3]. Nearly 10.8% of all deaths in India are attributed to hypertension [4].…”
Section: Introductionmentioning
confidence: 99%
“…While it is important to receive treatment for hypertension, it is also important to receive treatment that is effective. Uncontrolled hypertension is associated with an increased risk of myocardial infarction, heart failure, stroke, chronic kidney disease, and cognitive decline [8][9][10][11] and increased risk of mortality from cardiovascular disease [3,12]. A person is said to have resistant hypertension when there is a failure to achieve goal blood pressure in spite of adhering to full doses of an appropriate three-drug regimen that includes a diuretic [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is closely linked to cardiovascular disease [19], diabetes [20], and kidney disease [21]. By 2030, the estimated number of global deaths due to cardiovascular disease caused by high blood pressure will surge, and the annual death toll is expected to reach 23.6 million [22]. A study shows that three-quarters of diabetic patients tend to have high blood pressure, and patients with both high blood pressure and diabetes have a much higher probability of developing cardiovascular disease and a fourfold increase in mortality [23].…”
Section: Introductionmentioning
confidence: 99%
“…; World Health Organization ; Zhou et al. ). In Thailand, older men face a significantly higher prevalence of hypertension than older women (Chongthawonsatid ).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the prevalence of hypertension is more than 1.1 billion which rises from 594 million (Forouzanfar et al 2017), especially among an older adult population and men (World Health Organization 2018;Yang et al 2017). Among those, over 1 billion experience uncontrolled hypertension (Rouf et al 2018;World Health Organization 2018;Zhou et al 2018). In Thailand, older men face a significantly higher prevalence of hypertension than older women (Chongthawonsatid 2015).…”
Section: Introductionmentioning
confidence: 99%